Child rearing workplace policy for working mothers: A scoping review - Deandra, Fadhila Iswi; Februhartanty, Judhiastuty; Mansyur, Muchtaruddin (Indonesian Nutrition Association, 2024)
Introduction: Straddling work and childcare harms working moms' health, potentially their children too. To address this, child rearing workplace policies are needed. These would promote work-life balance and ensure both mothers' and children's well-being, ultimately protecting pregnant and parenting women at work. Objective: This study aims to explore the gaps between available child rearing workplace policy for working mothers and the implementation on the field while taking its implications into account. Methods: We reviewed literature from PubMed electronic database. Predefined keywords were developed and chosen. Relevant articles were filtered according to the inclusion and exclusion criteria. Furthermore, all articles were reviewed independently and those that match were included and charted through Microsoft Excel based on each articles’ characteristics. Results: There are 13 workplace policies related to childcare for working mothers in the included articles. The most common policy was paid maternity leave. Other frequently mentioned policies included lactation support and facilities, flexible work arrangements, and daycare facilities. All policies have different implementation rates and implications to both working mothers and their children. Conclusion: Supportive child rearing policies at work benefit everyone: employers, employees, and their families, leading to a better nutritional and health status, hence increase overall quality of life.